Prevalence, diversity and risk assessment of antibiotic resistant e. coli from anthropogenic impacted Larut River and Sangga Besar River / Low Kyle Young - Low , Kyle Young (2022)
The rising emergence of rapidly evolving, multi-antibiotic resistant Escherichia coli (E. coli) remained a global public health concern. Aquatic ecosystems under frequent anthropogenic influence could serve as reservoirs that provide an ideal condition for the acquisition and dissemination of antibiotic resistant genetic determinants. To better understand the impact of anthropogenic wastewater towards the occurrence, genetic diversity and virulence of antimicrobial resistant E. coli as well as their resistance genes, surface waters from riverine estuarine waters of Larut River and Sangga Besar River were studied. Six sampling sites situated upstream and downstream of the Larut River including wastewater from zoo, hospital, and slaughterhouse, along with three sites from neighbouring Sangga Besar River were studied. Concentrations and ecological risk of 22 antibiotics from surface water samples were quantified by solid phase extraction and high performance liquid chromatography tandem mass chromatography. Total coliform and E. coli were isolated and enumerated by membrane filtration technique. Antibiogram was profiled using antimicrobial susceptibility test (AST), whereas phylogeneticity, virulence gene, and antibiotic resistance gene were determined by multiplex PCR assays. Canonical correlation analysis (CCA) was then performed to analyse the E. coli phylogenetic groups against resistance genes sul and tet, physicochemical parameters, and antibiotic residue concentrations. Sixteen antibiotic residues were detected, with concentrations ranging from limit of detection (LOD) to 1,262.3 ng l-1 with residues of erythromycin, clarithromycin, and ofloxacin in hospital and zoo effluents posing a high risk to algae while tetracycline had low to medium ecological risks toward all the relevant organisms from aquatic environments (algae, invertebrate Daphnia magna, and fish). E. coli abundance at Larut River ranged from EST 1 to 4.1 × 105 CFU 100 ml-1, whereas Sangga Besar River ranged from EST 1 to 2.5 × 103 CFU 100 ml-1. All phylogenetic groups except B1 had non homogenous distribution, with phylogenetic group A, found significantly higher in effluents of hospital (58.57 %) and slaughterhouse (49.18 %) followed by S1b (51.67 %). Also, more than half of the E. coli isolates from Larut and Sangga Besar River have multiple antibiotic resistances. The prevalence of multiple antibiotic resistance phenotypes of E. coli with the presence of tet and sul resistance genes was higher in wastewater effluents compared to river waters. The phylogenetic composition of E. coli and resistance genes were associated with physicochemical properties and antibiotic residues. Findings conclude that sites impacted by wastewater effluents along with antibiotic residues had affected E. coli phylogenetic composition, antibiotic resistance phenotype diversifications, and resistance genes distribution in Larut River.